Impact of Profitability on Earnings Management in Industrial Companies Listed in Amman Stock Exchange - AbuJebbeh, Mohammed; AlThuneibat, Ali (Jordan Journal of Business Administration, 2017)
The purpose of this study is to identify the impact of profitability on the earnings management in the industrial companies listed in Amman Stock Exchange, through measuring the impact of the independent variables (profit margin, return on assets, return on equity and earnings per share) on the dependent variable (earnings management). The researchers used a quantitative standard approach in the analysis of financial statements to measure the company’s profitability. Jones modified model was used to measure the discretionary accruals as a proxy for earnings management. Simple and multiple linear regression models were used to test the hypotheses of the study. The study sample consisted of (40) industrial companies listed in Amman Stock Exchange which have been continuously trading during the period (2009-2013). The study results showed that there is a statistically significant effect for the independent variables (profit margin ratio, return on assets, return on equity and earnings per share) on earnings management. However, the results showed that there was no significant effect for debt ratio and the size of the company on the relationship between profitability and earnings management. Based on the results of the study, the researchers set many recommendations. The most important recommendations are to enhance the role of Amman Stock Exchange in monitoring the listed companies and take the appropriate legal requirements to prevent these companies from practicing earnings management that may mislead the users of financial statements.